Effectiveness of Physics Teaching Material Based on Contextual Static Fluid Material - Tri Ariani; Yaspin Yolanda (Kasuari: Physics Education Journal (KPEJ), 2019)
This study aims to determine the learning outcomes of class XI students in Lubuklinggau 6 Model State Senior High School 2018/2019 Academic Year after using contextual-based Physics teaching material for Static Fluid students and to find out the students' response to learning using contextual learning material Static Fluid class XI students in high school Negeri 6 Lubuklinggau Model 2018/2019 Academic Year. The sample of this study consisted of 23 students of class XI IPA 4 of State Senior High School 6 Model Lubuklinggau. Data collection is done by interview techniques, questionnaires, tests, and observations. The overall percentage of teaching material components is 81.82% (very good). The percentage of student responses to contextual-based teaching materials is 79.78% (very good). In addition, from the results of daily test results, the effectiveness percentage of 86.95% (very good) of students who received scores above 70 out of 10 test items. Data analysis technique used was t-test Calculated value> t table with the value of t count = 3.69 and t table = 1.717. The results of the average percentage of students in the affective realm of 89.40% (very good) and the results of the average percentage of students in the psychomotor realm of 91.30% (very good). The percentage of student responses to learning using contextual learning is 91.07% (very good). So that the use of contextual based teaching materials can be said to be valid, practical and effective.